COGNITIVE-BEHAVIOUR MODIFICATION: KEMANJURAN TEKNIK SELF-INSTRUCTION SEBAGAI MEDIA UNTUK MENINGKATKAN MOTIVASI BERPRESTASI PESERTA DIDIK - Prayogi, Fiki; Utomo, Prio (LPPM STKIP PGRI Bandar Lampung, 2021)
This research is motivated by the phenomenon of the problem that shows the low achievement motivation of students in school. The purpose of this study was to examine the effectiveness of using self-instruction techniques as a medium to increase student achievement motivation. The research design used pre-experimental design, the research method used one group pretest and posttest design. The research subjects were students of class XI SMA Adiguna Bandar Lampung with a total of 10 students, subjects were selected using purposive sampling technique. The research instrument uses; (1) treatment materials, (2) achievement motivation scale, and (3) observation guidelines. Data analysis used nonparametric analysis with Wilcoxom Signed Rank Test statistical test. The results of hypothesis testing show that H0 is rejected and H1 is accepted, this result indicates that there is an increase in students' achievement motivation after being given self-instruction techniques. The conclusion of the research shows that the self-instruction technique is effective and can be used as a medium to increase students' achievement motivation